Enhanced Sb2S3 crystallisation by electric field induced silver doping - Dong, Weiling; Krbal, Miloš; Kalikka, Janne; Chin, Xin Yu; Gholipour, Behrad; Soci, Cesare; Fons, P.J.; Mitrofanov, Kirill V.; Chen, Lujie; Simpson, Robert E. (My University, 2016)
This work reveals that doping Ag into Sb2S3 substantially decreases its crystallisation temperature. Weshowthat applying an electric field to Sb2S3 through Ag electrodes provides control of the crystallisation temperature and crystallisation rate. The crystal nuclei incubation time decreases substantiallywhen the applied electric field is set to 200 kV/m. The applied electric field appears to force the Ag cations through the amorphous chalcogenide film resulting in Ag doped Sb2S3 filaments that extend from the cathode to the anode. This was confirmed by X-ray fluorescence composition mapping. Density functional theory molecular dynamics modelling of Ag doped Sb2S3 reveals that the diffusion constant of Ag is twice that of Sb or S over a wide temperature range, which implies that the Ag atoms are mobile in the amorphous Sb2S3 structure. The applied electric field provides a mechanism to enhance the crystallisation kinetics of Ag-doped Sb2S3.
Zesílená krystalizace Sb2S3 elektrickým polem indukovaným dotací stříbra
Keywords: Sb2S3; Chalcogenide; Dissolution; Crystallisation; Sb2S3; chalkogenid; rozpouštění; krystalizace